Hydrostatic pressure effects on the Γ–X conduction band mixing and the binding energy of a donor impurity in GaAs–Ga1–xAlxAs quantum wells (2007)
ABSTARCT: Mixing between Γ and X valleys of the conduction band in GaAs–Ga1–xAlxAs quantum wells is investigated taken into account the effect of applied hydrostatic pressure. This effect is introduced via the pressure-dependent values of the corresponding energy gaps and the main band parameters. The mixing is considered along the lines of a phenomenological model. Variation of the confined ground state in the well as a function of the pressure is reported. The dependencies of the variationally calculated binding energy of a donor impurity with the hydrostatic pressure and well width are also presented. It is shown that the inclusion of the Γ–X mixing explains the non-linear behavior in the photoluminescence peak of confined exciton states that has been observed for pressures above 20 kbar. (© 2007 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)